Functional outcome following coracoclavicular ligament reconstruction using a gracilis tendon graft for acute type III acromioclavicular dislocation: a case report - Sidharta, Made Tusan; Wien Aryana, I. Gusti Ngurah; Arimbawa, Ida Bagus Gede (International Journal of Research in Medical Sciences, 2018)
The acromioclavicular joint is stabilized by two ligaments: the acromioclavicular ligaments and coracoclavicular ligaments. AC joint dislocations account for 9% to 10% of all shoulder injuries. Tossy and Allman classified acromioclavicular dislocations into three types (I, II and III). This classification was modified by Rockwood (types IV, V, and VI). Type I and II dislocations are treated conservatively. Surgery is indicated for certain Rockwood type III and for all type IV, V, and VI injuries. A 45 years old man yoga trainer presented to our emergency department with a chief complaint of pain over his left shoulder after had traffic accident 3 hours prior to admission. Physical examination revealed left lateral clavicular end prominent and tenderness over the left shoulder with limited range of motion due to pain. A Zanca view X-Ray of left shoulder was performed and revealed dislocation of acromioclavicular joint. The patient was diagnosed with suspect Left AC joint disruption grade III. We performed coracoclavicular ligament reconstruction using a gracilis tendon graft 2 days after the accident. Before the surgery, constant score of the patient left shoulder was 25 (Fair). The constant score measured was 63 after 10 month follow up. Coracoclavicular ligament reconstruction with an autogenous gracilis tendon graft was feasible and safe in physically active patients with acute type-III acromioclavicular joint dislocation.